Protection motivation theory in predicting intentional behaviors regards schistosomiasis: a WeChat-based qualitative study - Wang, Yi; Li, Chengyuan; Zhang, Jianfeng; Mao, Yuanchun; Li, Wei (Frontiers in Public Health, 2024)
Background:Modifications of behavior can help reduce the risk of transmission by disrupting the parasite life cycle. Behavior intension is a necessary intermediate step in behavior change.This study aimed to explore protection motivation theory (PMT) in predicting likelihood of engagement in protective behavior against infection with Schistosoma.Methods:In China, a questionnaire for data collection was sent to users who followed the WeChat public account from June 2 to 6, 2023. Factors affecting intentional behavior of participants were analyzed using stepwise regression analysis and structural equation modeling.Results:A total of 2243 valid questionnaires were collected, with a mean age of 30 ± 8.4 years.Approximately 1395(62.2%) participants reported that they had been exposed to wild waters in daily work and life.About 51.0% and 50.7% of respondents reported never having been exposed to wild water in the last 3 and 6 months, respectively.Results indicated that prior knowledge of schistosomiasis was associated with the 7 PMT subconstructs, which then influenced future preventative behaviors.Conclusions:Behavior intentionis a complicated and indispensable partof behavior change that is influenced by professional knowledge, socio-economic status,and personal characteristics. The effective dissemination ofknowledge regards schistosomiasis should be strengthened to emphasize the effectiveness of protective measures against infection and severe disease.